Interpersonal Communication of Bengkulu Athletes to Coaches Towards Pon Papua 2021 - Yahya Eko Nopiyanto; Bogy Restu Ilahi; Septian Raibowo; Andika Prabowo; Ibrahim Ibrahim (Universitas PGRI Palembang, 2023)
This study aims to describe the interpersonal communication built by Bengkulu athletes to their coaches in the preparation period for PON Papua 2021. Quantitative descriptive research methods were used in this study. The study population was 83 Bengkulu athletes who were prepared to participate in PON Papua 2021. Sampling in this study was a total sampling so that all athletes became a sample of 83 athletes. The data collection technique used a questionnaire, and the instrument used was the coach-athlete relationship questionnaire. The research instrument consists of three aspects, namely: closeness, orientation, and complementarity. The validity of the instrument used was 0.463-0.721 and the reliability was 0.92. The research data were processed using the mean ideal and standard deviation ideal. The results of the study stated that the interpersonal communication between Bengkulu athletes and their coaches had a score of 41.40-46.00 in the very good category, so it was concluded that the interpersonal communication of Bengkulu athletes to the coach towards Pon Papua 2021 was in the very good category.Â